Non-psychotic mental and cognitive disorders in epileptic patients with persistent seizure control and their dynamics in the treatment process - S. A. Gromov; L. V. Lipatova; O. N. Yakunina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Scientific explanation of the gradual relief of mental disorders in patients with prolonged control of seizures in the regression of epileptic patterns on EEG and the symptoms of epileptogenesis. Materials and methods. We studied 239 patients with epilepsy (PE) and 120 patients with long-term control of seizures, used methods of clinical observation, MRI, EEG, and 12 experimental psychological methods. Results. It is established that a persistent seizure control determines the positive dynamics of indicators of mental activity of PE. Conclusion. The cessation of seizures determines the positive dynamics of indicators of mental state of PE. The degree of regression of personality changes should considered in decision making about the withdrawal period treatment of anti-epileptic drugs and practical recovery from epilepsy.